2023
DOI: 10.1037/xap0000475
|View full text |Cite
|
Sign up to set email alerts
|

People are worse at detecting fake news in their foreign language.

Rafał Muda,
Gordon Pennycook,
Damian Hamerski
et al.

Abstract: Across two preregistered within-subject experiments (N = 570), we found that when using their foreign language, proficient bilinguals discerned true from false news less accurately. This was the case for international news (Experiment 1) and more local news (Experiment 2). When using a foreign (as opposed to native) language, false news headlines were always judged more believable, while true news headlines were judged equally (Experiment 2) or less believable (Experiment 1). In contrast to past theorizing, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…What is more, number of listed thoughts did not differ between languages what clearly indicate that the foreign language effect does not arise (at least in our study) due to decreased fluency and processing difficulties leading to greater engagement of reflective processes. This is consistent with much of the past work also not finding the support for any of the two proposed explanations behind the foreign language effect, e.g., changes in affective response to news were not mediating the ability to discern true from false news (Muda et al, 2023) or moral judgments (Hadjichristidis et al, 2015;but see Kyriakou et al, 2022). Using a foreign language also did not benefit reasoning (Białek et al, 2020), performance in various heuristic-andbiases tasks (Maekelae & Pfuhl, 2019), in cognitive reflection test (Białek et al, 2019;Costa et al, 2014;Milczarski et al, 2022) or numeracy test (Milczarski et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…What is more, number of listed thoughts did not differ between languages what clearly indicate that the foreign language effect does not arise (at least in our study) due to decreased fluency and processing difficulties leading to greater engagement of reflective processes. This is consistent with much of the past work also not finding the support for any of the two proposed explanations behind the foreign language effect, e.g., changes in affective response to news were not mediating the ability to discern true from false news (Muda et al, 2023) or moral judgments (Hadjichristidis et al, 2015;but see Kyriakou et al, 2022). Using a foreign language also did not benefit reasoning (Białek et al, 2020), performance in various heuristic-andbiases tasks (Maekelae & Pfuhl, 2019), in cognitive reflection test (Białek et al, 2019;Costa et al, 2014;Milczarski et al, 2022) or numeracy test (Milczarski et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…These outcomes align with much of the prior work with much of the prior research, which similarly fails to provide support for either of the two proposed explanations behind the foreign language effect. For instance, changes in affective responses to news were not found to mediate the effects of using a foreign language on neither the ability to distinguish true from false news (Muda et al, 2023) nor moral judgments (Hadjichristidis et al, 2015;but see Kyriakou et al, 2022). Using a foreign language also did not benefit reasoning (Białek et al, 2020), performance in various heuristicand-biases tasks (Maekelae & Pfuhl, 2019), in cognitive reflection test (Białek et al, 2019;Costa et al, 2014;Milczarski et al, 2022) or numeracy test (Milczarski et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…As the research on the foreign language effect progresses, the effect appears more complex and malleable than initially hoped. For example, we found no foreign language effect on risky choice ( Borkowska et al 2023 ; Muda et al 2020 ) and using a foreign language has been shown to distort the ability to delay gratifications ( Białek et al 2022 ), reason logically ( Białek et al 2020 ) or the ability to discern true from false news ( Muda et al 2023 ). Numerous studies from other labs are also reporting no effects of using a foreign language on decision-making.…”
Section: The Foreign Language Effectmentioning
confidence: 71%
“…The first speculation was that people using their foreign language experience lower affective arousal than those using their native language. Dedicated studies showed that although people using their foreign language are sometimes less aroused by the problem they face, this change in arousal was not predicting the decision change ( Geipel et al 2015b ; Hadjichristidis et al 2015 ; Muda et al 2023 ). However, in one research this hypothesis was confirmed, showing that people using their foreign language when solving moral dilemmas used less affect-rich vocabulary, and this change predicted their shift to more outcome-based responding ( Kyriakou et al 2022 ).…”
Section: The Mechanisms Of the Foreign Language Effectmentioning
confidence: 99%
“…However, the current work parallels recent research on MFLE indicating that processing dilemmas in one’s FL does not enhance utilitarian responding but instead can reduce deontological and sometimes also utilitarian responding. In addition, some studies have shown that processing in FL may be impaired in tasks that involve mental imagery [ 67 ], identifying logically invalid syllogisms [ 55 ] and ‘fake news’ [ 68 ], as well as judging hazards such as smoking and climate change [ 69 ].…”
Section: Discussionmentioning
confidence: 99%